Working Capital in the Telecom Industry - Laureano, L.; Neves, Luís; Laureano, Raul M. S. (5th Global Management Conference, 2013)
We examine the relationship between profitability and efficiency of working capital management in the telecommunication services industry. Our sample consists of 48 companies classified by Reuters® as Integrated Telecommunication Operators, resulting in 488 firm-year observations for the period 1998-2009. We find evidence that the Net Trade Cycle is a better measure of efficiency of working capital management in the telecommunication industry, when compared with the Cash Conversion Cycle. Increasing the Net Trade Cycle represents an enhancement in the profitability of the telecom operators. This increase at the Net Trade Cycle level can be generated by reducing the number of day sales of accounts payable.